Present‐day stress states underneath the Kumano basin to 2 km below seafloor based on borehole wall failures at IODP site C0002, Nankai accretionary wedge. (2nd November 2016) - Chang, Chandong; Song, Insun
Abstract: We constrain the state of stress to 2 km below seafloor in the Nankai accretionary prism at the Integrated Ocean Drilling Program (IODP) site C0002F, southwest Japan, based on borehole wall failures and rock strengths. The logging‐while‐drilling resistivity images from 872.5 to 2005.5 m below seafloor show that drilling‐mud control in riser drilling worked properly to minimize borehole wall failures. Available breakouts indicate a consistent maximum compression orientation subparallel to the subducting plate margin. Breakout analysis with drill logs suggests that breakouts occurred only when borehole pressure was slightly lowered and time lag between hole cutting and image logging was several hours. This indicates that the observed breakouts are not immediate stress‐induced failure but brought up into shape gradually with time due to other mechanisms. Laboratory investigations on deformation and failure of the cores suggest that the time‐delayed breakout might be a result of progressive rock spall‐out in borehole wall damage zones that occur at a stress level close to failure condition. We constrain stress magnitudes assuming that the stress state is sufficient to bring about the damage zones at the borehole wall. An integrated method utilizing breakouts, drilling‐induced tensile fractures, and a leak‐off test suggests that the stress states are on the boundary between strike‐slip faulting and normal faulting stress regimes, and somewhat variable depending on depth. The stress magnitudes in the accretionary wedge appear to be controlled by frictional strength of the rock, such that the differential stresses are constrained by the laboratory determined frictional coefficients. Key Points: The present‐day state of stress at Nankai accretionary prism is constrained by borehole failure analysis and leak‐off test The observed breakouts are not stress‐induced immediate borehole failure, but rather brought up into shape gradually with time The stress state varies between strike‐slip and normal faulting favored stress regime